Bioethics and biosafety in dentistry care for patients with HIV / aids - Yarelys Sans Cueto; Mallen Martínez Rodríguez; Orlando Blanco Hernández; Dunia Milagros Labrador Falero; Yoerlandy Acosta Lopez (Revista de Ciencias Médicas de Pinar del Río, 2017)
Introduction: acquired immunodeficiency syndrome (AIDS) is not a single disease, but the final stage of HIV infection, characterized by a set of potentially fatal diseases.